Dopamine versus noradrenaline in septic shock - Xu, BO (Australasian Medical Journal, 2011)
BACKGROUND: The ‘ Surviving Sepsis’ Campaign guidelines recommend the use of dopamine or noradrenaline as the first vasopressor in septic shock. However, information that guides clinicians in choosing between dopamine and noradrenaline as the first vasopressor in patients with septic shock is limited. OBJECTIVE: This article presents a review of the literature regarding the use of dopamine versus noradrenaline in patients with septic shock. RESULTS: Two randomised controlled trials (RCT) and two large prospective cohort studies were analysed. RCT data showed dopamine was associated with increased arrhythmic events. One cohort study found dopamine was associated with higher 30-day mortality. The other cohort study found noradrenaline was associated with higher 28-day mortality. DISCUSSION: Data on the use of dopamine versus noradrenaline in patients with septic shock is limited. Following the recent SOAP II study, there is now strong evidence that the use of dopamine in septic shock is associated with significantly more cardiovascular adverse events, compared to noradrenaline. CONCLUSION: Noradrenaline should be used as the initial vasopressor in septic shock to avoid the arrhythmic events associated with dopamine.